Social Isolation Is Associated With the Acceleration of Death and Incident Cardiovascular Disease in Adults With Chronic Kidney Disease - Xiaoxi Zeng; Yifan Jiang; Zhongyu Liu; Huazhen Yang; Huan Song; Chunyang Li; Ping Fu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Individuals with chronic kidney disease are at markedly increased risk of incident cardiovascular diseases (CVDs) and premature death. The impact of social isolation on adverse outcomes in chronic kidney disease remained understudied. Methods This prospective cohort study included 13 090 individuals with chronic kidney disease from the UK Biobank. The exposure was social isolation categorized into 3 levels: least, moderately, and most isolated. Using accelerated failure time and restricted mean survival time analyses. Results Compared with being least isolated, moderate and most isolation are associated with the acceleration of all‐cause death with a time ratio of 0.87 (95% CI, 0.82–0.93; P<0.001) and 0.76 (95% CI, 0.70–0.82; P<0.001), respectively, and restricted mean survival time differences of 49.1 and 71.6 days within 10 years. We observed marginal association of moderate (time ratio, 0.93 [95% CI, 0.87–0.99]; P=0.039) and most isolation (time ratio, 0.87 [95% CI, 0.79–0.96]; P=0.005) with CVD. But the association was significant only for stroke, not for coronary artery disease. Based on pathways revealed by a directed acyclic graph constructed using the Bayesian network, we conducted inverse odds ratio–weighted mediation to decompose the total effect of social isolation on death, and found that CVD and sarcopenia mediated 21.8% (95% CI, 7.1–43.0) of the total effect of social isolation on death. Conclusions Social isolation is associated with shortened survival and accelerates the onset of CVD in individuals with chronic kidney disease. Social support warrants attention in the prevention of death and CVD in these high‐risk individuals.